Analysis of Customer Trust and Satisfaction on Service Quality and Security of BSI Mobile Customers After Cyber Banking - Lestari Lestari; Ahmad Fauzul Hakim Hasibuan; Auliyah Chairani; Putri Rahmadhani (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
This study uses qualitatif methods with interviews. So the basis for this research is the author’s interpretation of customer trust and satisfaction in BSI Mobile customers quality of service and security after cyber banking, which explains how customer trust in BSI Mobile. according to the purpose of this study, the researchers wanted to see how the response of BSI customers when cyber banking issues arose the object of research in this study consisted of 3 people, namely 2 women and 1 man who were BSI customers who used transfers. the results of the study show that they agree that the E-banking feature, in which the informants say the same and different opinions, they agree that the features offered in mobile banking are new conveniences